Workshop Klinis: Trik Lolos PKM (Program Kreativitas Mahasiswa) untuk Mahasiswa Se-Karesidenan Madiun - Harida, Ratri; Kartikaputra, Tomy; Arkam, Rohmad; Ro'is, Syamsuddin (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2025)
Based on documentation studies at STKIP PGRI Ponorogo, there is the fact that the quantity of PKM proposal submissions in 2023 is <70% of last year's DIKTI PKM acceptance quota. This fact needs special attention so that the proposal acceptance quota can be utilized optimally and utilized by students. Of course, this fact must be followed up immediately in the form of a clinical workshop activity for preparing PKM proposals with the theme